2020
DOI: 10.1111/coa.13561
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory airflow obstruction due to tracheostomy tube: A spirometric study in 50 patients

Abstract: Objectives Tracheostomy is commonly used in intensive care units and in head and neck departments. Airway obstruction due to occluded cuffless tracheostomy tubes themselves remains unknown, although capping trials are commonly used before decannulation. The aim of this study was to evaluate the extent to which airway obstruction can be caused by occluded cuffless tubes in patients who underwent head and neck surgery. Design Prospective Research Outcome. Settings University teaching hospital. Participants Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…They used a portable spirometer to measure vital capacity, forced expiratory volume, and peak flow rate in two settings before and immediately after decannulation through mouth breathing. They found a significant increase of studied respirometer parameters after decannulation and concluded that capped tracheostomy causes a remarkable airflow obstruction, mostly in the expiratory phase [16].…”
Section: Discussionmentioning
confidence: 97%
“…They used a portable spirometer to measure vital capacity, forced expiratory volume, and peak flow rate in two settings before and immediately after decannulation through mouth breathing. They found a significant increase of studied respirometer parameters after decannulation and concluded that capped tracheostomy causes a remarkable airflow obstruction, mostly in the expiratory phase [16].…”
Section: Discussionmentioning
confidence: 97%
“…In a clinical spirometry investigation, a dramatic airflow obstruction was found, mainly in expiration, due to occluded TTs during capping trials [ 6 ]. There are no standardized recommendations for decannulation and capping.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has shown the use of capping for assessing readiness for decannulation in 63.7% of the patients [ 5 ]. However, capped TTs create an impairment of airflow [ 6 ]. Therefore, test decannulation using a SB may be performed [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In young children, the smallest tracheostomy tube may completely fill the trachea and capping trials are generally recommended for children 2 years or older 25 . The tracheostomy tube occupies a significant percentage of the airway and thereby decreases the cross‐sectional area of the trachea, limits airflow, 26 and increases airway resistance. The occluded tracheostomy can then lead to increased respiratory effort 27 favoring collapse of the oropharyngeal tissues.…”
Section: Conmentioning
confidence: 99%